White coats in the ghetto : Jewish medicine in Poland during the Holocaust - Offer, Miriam, 1960- 1960- (Yad Vashem publications, 2020)
White Coats in the Ghetto narrates the struggle of the Jews to survive in the Warsaw ghetto while also preserving their humanity during the Holocaust. Based on a vast quantity of official and personal documents, it describes the elaborate medical system that the Jews established in the ghetto to cope with the lethal conditions imposed on them by the Nazis, and the tragic ethical dilemmas that the medical teams confronted under German occupation. -- Publisher description